THE DESCRIPTION OF TEACHER’S THINK ALOUD STRATEGY IN TEACHING READING COMPREHENSION AT TENTH GRADE OF SMK NEGERI 1 SITOLU ORI IN 2022/2023 - Ziliwu, Erdin; Laoli, Adieli; Harefa, Afore Tahir; Telaumbanua, Yasminar Amaerita (Academy of Education Journal, 2023)
The aim of research is to describe the using of teacher’s Think Aloud Strategy in Teaching Reading Comprehension and to describe the advantages and disadvantages of Think Aloud Strategy in Teaching Reading Comprehension for students. In conducting the research, the researcher used qualitative research. The result showed that the implementation of Think Aloud Strategy by teacher adapted from theory of Bahri, et al. (2018). There were 6 activities that have been done and 1 activity that has not been done by teacher. The advantage of using Think Aloud Strategy in teaching reading comprehension were students more quickly find main ideas from text, improves students' way of thinking, students are active in learning, and students get new vocabulary. The disadvantage of Think Aloud Strategy were not all students could follow this strategy especially in giving opinion and students whose level of understanding is lack need the long time to answer questions.